Impact of mobile social media advertising and role of culture on brand equity among Gen-Y consumers in the United Arab Emirates - Al Kindi, Majed Zamil Hatem (2017)
Consumers of the Generation-Y cohort, also referred to as Millennials, born between 1981-1999, include approximately 45% of the population in United Arab Emirates, who have significant purchasing power. These consumers access social media on a daily basis, but they often ignore brand advertisements that target them. This thesis aims to investigate the causes why Gen-Y ignore mobile social media advertising. United Arab Emirates is a multicultural society; Dubai, its economic center, was chosen for this research because of its cultural diversity, and unique population, where locals represent only 20% of the total population, with expatriates comprising the other 80%. The purpose of this quantitative study of mobile social media advertising and/or marketers on brand equity in the United Arab Emirates is to determine successful strategies to engage Generation-Y on mobile social media, The choice of mobile social media advertising is because, at the time of this study, there has not been any systematic advertising technology model available for mobile social media in UAE. The finding of the study revealed a significant positive relationship between Gen-Y attitude (p <. 05), mobile social media advertising (p <. 05), culture (p <. 05) and brand equity. Moreover, the findings showed that Gen-Y attitude, mobile social media advertising, and culture are significant predictors of brand equity. However, the standardized indirect effect test based on bootstrap technique have shown that Gen-Y attitude partially mediates the relationships between mobile social media advertising, culture and brand equity. The results also indicated a significant difference in culture based on the respondent’s regional distribution. Finally, the result indicated that culture moderates the relationship between mobile social media advertising and attitude with brand equity. This study may contribute to social change by improving the relationship between social media advertising and marketers on brand equity among Gen-Y consumers, permitting Gen-Y consumers to gain a stronger voice in marketing, and by emphasizing the need for marketers to communicate and advertise more effectively with Gen-Y.